2002
DOI: 10.1021/jf020568m
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cholesterol from Cheddar Cheese by β-Cyclodextrin

Abstract: This study was carried out to determine the cholesterol removal rate and resulting changes in flavor, fatty acid and bitter amino acid production in reduced-cholesterol Cheddar cheese, made by cream separation followed by 10% beta-cyclodextrin (beta-CD) treatment. The cholesterol removal from the cheese was 92.1%. The production of short-chain free fatty acids (FFAs) increased the ripening time in control and cream-treated cheeses. The quantity of short-chain FFAs released between treatments during ripening wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 21 publications
5
67
0
Order By: Relevance
“…However, most of these methods are relatively non-selective and remove flavour and nutritional components when cholesterol is removed. Moreover, some methods require high investment and operation costs (Yen and Tsai 1995;Kwak et al 2002). Research studies show that cholesterol can be removed from milk and dairy products, egg yolk, lard, by using b-cyclodextrin (b-CD) (Yen and Tsai 1995;Krause et al 2007;Lee et al 2007;Seon et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these methods are relatively non-selective and remove flavour and nutritional components when cholesterol is removed. Moreover, some methods require high investment and operation costs (Yen and Tsai 1995;Kwak et al 2002). Research studies show that cholesterol can be removed from milk and dairy products, egg yolk, lard, by using b-cyclodextrin (b-CD) (Yen and Tsai 1995;Krause et al 2007;Lee et al 2007;Seon et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…b-CD has also advantages of non-toxicity, edibility, non-hygroscopicity, chemical stability and easy separation (Kwak et al 2002). Thus it may be a suitable substance for cholesterol removal from foods.…”
Section: Introductionmentioning
confidence: 99%
“…These properties allow them to form non-covalent inclusion complexes by encapsulating of variety of 'guest' molecules into the 'host' which refer to their central cavities through associate and dissociating process. Kim et al [24] and Kwak et al [30] reported the protein reduction in milk after removal of cholesterol. It was confirmed that the protein content of cream was reduced during reduction of cholesterol by 4 -10 % -CD due to entrapment of amino acids in -CD cavities [29].…”
Section: Protein Quantificationmentioning
confidence: 99%
“…β-CD is non-toxic, edible, non-hygroscopic and chemically stable. In previous years, studies have indicated that β-CD can be used to reduce cholesterol effectively from food products (Kwak et al 2002;Shim et al 2003;Hwang et al 2005;Lee et al 2007). In most of these reports, powdered β-CD was used and it allows about 90 % of the cholesterol to be removed but separation and collection of β-CD after completion of process is a time consuming and laborious task.…”
Section: Introductionmentioning
confidence: 99%